2011
DOI: 10.1371/journal.pone.0022333
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Long-Term Modulation of Neuropeptide Y in Hypothalamic Arcuate Nucleus Induces Energy Balance Alterations in Adult Rats

Abstract: Neuropeptide Y (NPY) produced by arcuate nucleus (ARC) neurons has a strong orexigenic effect on target neurons. Hypothalamic NPY levels undergo wide-ranging oscillations during the circadian cycle and in response to fasting and peripheral hormones (from 0.25 to 10-fold change). The aim of the present study was to evaluate the impact of a moderate long-term modulation of NPY within the ARC neurons on food consumption, body weight gain and hypothalamic neuropeptides. We achieved a physiological overexpression (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 95 publications
(127 reference statements)
1
40
0
1
Order By: Relevance
“…The NPY serum levels observed in our normal rats are similar to those found in other studies in rats (32) and slightly higher than those observed in humans (35,36). We propose that the decrease in serum NPY levels observed in BDL rats may be due to reduced secretion of NPY by the neural tissue of the central and peripheral nervous system (38).…”
Section: Discussionsupporting
confidence: 89%
“…The NPY serum levels observed in our normal rats are similar to those found in other studies in rats (32) and slightly higher than those observed in humans (35,36). We propose that the decrease in serum NPY levels observed in BDL rats may be due to reduced secretion of NPY by the neural tissue of the central and peripheral nervous system (38).…”
Section: Discussionsupporting
confidence: 89%
“…To evaluate the effect of NPY on hypothalamic autophagy modulation in vivo, NPY was overexpressed in hypothalamic arcuate nucleus (ARC) by gene transfer using adeno-associated viral vectors (AAV), in male C57BL/6 mice. Mice were injected with AAV encoding either GFP (AAV-GFP, control group) or NPY (AAV-NPY), under a neuronal-specific promoter (36), by bilateral stereotaxic injection in each ARC. After 4 wk, hypothalamic NPYoverexpressing mice (AAV-NPY mice) brains displayed a stronger, widespread expression of NPY through the several hypothalamic areas, but still more pronounced in the ARC (Fig.…”
Section: Significancementioning
confidence: 99%
“…7B, we observed an increase of ∼70% of NPY immunoreactivity in the ARC in hypothalamic NPY-overexpressing mice compared with control mice (AAV-GFP; 172.5 ± 21.6% of control). We and others previously reported that hypothalamic NPY overexpression led to hyperphagia, increased body weight gain, and several serum alterations, consistent with obesity phenotypes, such as high glucose and high cholesterol (36). To avoid this type of effect that could potentially influence autophagy regulation (37,38), hypothalamic NPY-overexpressing mice were pair-fed, by giving the same daily amount of food that AAV-GFP mice consumed.…”
Section: Significancementioning
confidence: 99%
“…It also regulates TRH directly and indirectly: directly by opposing ␣-MSH activation of CREB signaling in TRH neurons and reducing pro-TRH processing by PC2, and indirectly by reducing the production and release of ARC ␣-MSH. We focus on ARC-derived NPY because NPY is produced most abundantly in the ARC (19,41); these neurons innervate the PVN (3) and POMC neurons (6,8,9), and ARC NPY has well-documented effects on food intake and body weight (64). NPY derived from other neurons could have the same influence on POMC and TRH, which merits future investigation.…”
Section: E647 Npy Regulates Pomc Processingmentioning
confidence: 99%
“…A recent study revealed the importance of ARC NPY in regulating energy balance, as moderate manipulation of NPY specifically in the ARC altered food intake and promoted positive energy balance (64). NPY neurons within the ARC innervate hypothalamic neurons involved in energy balance control, including cells in the PVN that produce the anorectic thyrotropin-releasing hormone (TRH) as well as cells within the ARC that produce the anorectic ␣-melanocyte-stimulating hormone (␣-MSH) (3,6,8,9).…”
mentioning
confidence: 99%